Fluorometric gene assay for determination of Escherichia coli 0157:H7 using graphene quantum dots and carbon dots with gold and silver nanoparticles - Mohd Saad, Suria (2020)
Escherichia coli (E. coli) O157:H7 is considered as harmful bacteria which can result in severe infections to human. Current detection methods are prolonged and inefficient due to extensive sample preparation and lengthy test procedures. Thus, there is a requirement for simplicity of techniques which are capable of sensing E. coli O157:H7 at high sensitivity, specific, less toxicity and agile. A fluorescence quenching assay involving graphene quantum dots (GQDs) and carbon dots (CDs) with gold (AuNPs) and silver (AgNPs) nanoparticles for the determination of E. coli O157:H7 have been explored. GQDs and CDs act as the fluorophore, while AuNPs and AgNPs as the quencher. Short target oligos (20 bp) have been utilized to establish distance between fluorophore and quencher in close proximity. Then, the fluorophore and quencher were complexing adjacently to trigger the fluorescence quenching mechanism following the target oligos co-hybridization. The complex immediately returns to the ground state by absorption of light without the release of photons. Several essential parameters such as reaction time and wavelength maximum of emission have been optimized to enhance the efficiency of fluorescence quenching. An excitation/emission wavelength of 400 nm/530 nm and 340 nm/450 nm were used for GQDs and CDs, respectively. The net intensity fluorescence quenching of GQDs and CDs was enhanced proportionally with the increment concentrations of target oligos. A linear correlation between the fluorescence quenching of GQDs/CDs and the logarithm concentration of target oligos in the series of 0.1 nM to 150 nM (GQDs-AuNPs), 0.01 nM to 200 nM (CDs-AuNPs) and 0.001 nM to 200 nM (CDs-AgNPs) (slope = 42.74, R2 = 0.991; slope = 675.6, R2 = 0.992; slope = 217.6, R2 = 0.977) and the detection limit (LOD) of 1.10 ± 0.58 nM, 1.00 ± 0.71 nM and 1.01 ± 0.71 nM, respectively. The proposed method was utilized for verification of selectivity and specificity towards different oligonucleotide sequence and bacteria strain with satisfactory results. The practicability of the assay was also verified by evaluating the amplicon (fliC gene, 381 bp) of genomic DNA isolated from food samples spiked with E. coli O157:H7. It is noteworthy that the determined t-value is less than the critical tvalue (tcalc. < 2.78) indicating that the developed method and real time PCR method are comparable and in good agreement.